A Self-Powered Breath Analyzer Based on PANI/PVDF Piezo-Gas-Sensing Arrays for Potential Diagnostics Application - Fu, Yongming; He, Haoxuan; Zhao, Tianming; Dai, Yitong; Han, Wuxiao; Ma, Jie; Xing, Lili; Zhang, Yan; Xue, Xinyu (Nano-Micro Letters, 2018)
The increasing morbidity of internal diseases poses serious threats to human health and quality of life. Exhaled breath analysis is a noninvasive and convenient diagnostic method to improve the cure rate of patients. In this study, a self-powered breath analyzer based on polyaniline/polyvinylidene fluoride (PANI/PVDF) piezo-gas-sensing arrays has been developed for potential detection of several internal diseases. The device works by converting exhaled breath energy into piezoelectric gas-sensing signals without any external power sources. The five sensing units in the device have different sensitivities to various gas markers with concentrations ranging from 0 to 600 ppm. The working principle can be attributed to the coupling of the in-pipe gas-flow-induced piezoelectric effect of PVDF and gas-sensing properties of PANI electrodes. In addition, the device demonstrates its use as an ethanol analyzer to roughly mimic fatty liver diagnosis. This new approach can be applied to fabricating new exhaled breath analyzers and promoting the development of self-powered systems. Highlights: 1 A self-powered breath analyzer based on polyaniline/polyvinylidene fluoride (PANI/PVDF) piezo-gas-sensing arrays was developed for a potential diagnostics application. 2 The device works by converting energy from exhaled breath into electrical sensing signals without any external power sources. 3 The working principle can be attributed to the coupling of in-pipe gas-flow-induced piezoelectric effect of PVDF bellows and gas-sensing effect of PANI electrodes.